2011
DOI: 10.1007/s00709-011-0285-2
|View full text |Cite
|
Sign up to set email alerts
|

Is callose a barrier for lead ions entering Lemna minor L. root cells?

Abstract: Plants have developed a range of strategies for resisting environmental stresses. One of the most common is the synthesis and deposition of callose, which functions as a barrier against stress factor penetration. The aim of our study was to examine whether callose forms an efficient barrier against Pb penetration in the roots of Lemna minor L. exposed to this metal. The obtained results showed that Pb induced callose synthesis in L. minor roots, but it was not deposited regularly in all tissues and cells. Call… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 34 publications
0
21
0
Order By: Relevance
“…It is thought that the permeability of plasmodesmata is actively regulated by the ATP-dependent sphincter, located in the neck regions of the plasmodesmata and/or by rapid reversible depositions of callose in the cell wall around the plasmodesmata (Radford and White 1998). It has been found that Pb induces the accumulation of callose within the plasmodesmata in Lemna minor roots (Samardakiewicz et al 2012). The presence of callose deposits observed in the cell walls of Pb-treated L. luteus roots may lead to the assumption that intercellular water transport through the plasmodesmata is limited, which in turn would favor water accumulation in the vacuoles (Rucińska-Sobkowiak et al 2013).…”
Section: Effects Of Heavy Metals On Water Uptakementioning
confidence: 99%
See 1 more Smart Citation
“…It is thought that the permeability of plasmodesmata is actively regulated by the ATP-dependent sphincter, located in the neck regions of the plasmodesmata and/or by rapid reversible depositions of callose in the cell wall around the plasmodesmata (Radford and White 1998). It has been found that Pb induces the accumulation of callose within the plasmodesmata in Lemna minor roots (Samardakiewicz et al 2012). The presence of callose deposits observed in the cell walls of Pb-treated L. luteus roots may lead to the assumption that intercellular water transport through the plasmodesmata is limited, which in turn would favor water accumulation in the vacuoles (Rucińska-Sobkowiak et al 2013).…”
Section: Effects Of Heavy Metals On Water Uptakementioning
confidence: 99%
“…The presence of metal deposits, e.g., Pb in L. luteus (Gzyl et al 1997) or Zn in P. vulgaris (Kasim 2007), occluding intercellular spaces and impregnating middle lamellae, may hamper apoplastic water flow. It was reported that Pb is involved in the formation of cell wall thickening (Krzesłowska 2011;Krzesłowska et al 2009), as well as in increases in lignin content in Glycine max (Pawlak-Sprada et al 2011) and Pisum sativum roots (Pb and As) (Päivöke 1983), callose in L. minor roots (Samardakiewicz et al 1996(Samardakiewicz et al , 2012 and in pectins, callose, cellulose, and sometimes the sudanophilic lipid compound in the protonemata of Funaria hygrometrica (Krzesłowska et al 2009;Krzesłowska and Woźny 2000). The formation of characteristic callose deposits was also observed as a general response of plants to many other metals: Ni, Co, Cr, Mn, Pb, Sr, As, Cd and Al (Piršelová and Matušíková 2013 and references therein).…”
Section: Effects Of Heavy Metals On Water Uptakementioning
confidence: 99%
“…Pb localization at the ultrastructural level was estimated using TEM because the conventional electron microscopy is often used as an adequate technique for analysing the distribution of electron-dense lead deposits in plant cells (Gzyl et al 1997; Krzesłowska and Woźny 1996; Samardakiewicz et al 2012; Wierzbicka 1995, 1998; Wierzbicka et al 2007). It was shown that less than 4 % of lead was lost during chemical preparation of tissues and the redistribution of lead was so insignificant that it did not affect the image seen in TEM (Antosiewicz and Wierzbicka 1999).…”
Section: Discussionmentioning
confidence: 99%
“…However, droughts, conditioning xylem embolism vessels, reduce water apoplast transport and increased consumption of energy and metabolites for transport them through symplast active or trans cellular route. In these conditions water transport is carried from cell to cell and transfer the apoplast is small [20]. Most of the water flow passes through the trans cellular pathway including transport through plasmodesma and trans membrane transport.…”
Section: General Remarksmentioning
confidence: 99%